(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2026)
In criminal law, adjudicating responsibility relies on two foundational capacities: the comprehension of the wrongful nature of the act and the ability to behave in accordance with this comprehension. These elements are subject to interpretation, often requiring the involvement of experts, although it is not uncommon the incidence of discrepancies among them. Brain-based mind reading technologies is principally aimed to enhance objectivity by analyzing brain metrics rather than observed behavior. While promising in addressing subjectivity, concerns remain about the limited reproducibility of the data and the brain’s complexities. The application of artificial intelligence offers potential solutions to these challenges; however, it concurrently introduces profound ethical and legal dilemmas.